Fluorine-free oil repellent coating, methods of making the same, and uses of the same

By using polysilicon siloxane-based materials and adding nanoparticles, a low surface tension, molecularly rough coating was developed, which solved the problem of difficult to develop a high-performance oil-water separation coating without fluorine compounds in the prior art, and achieved a coating effect with high washing resistance and durability.

JP2025037933APending Publication Date: 2025-03-18CORNELL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024205116
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-04-17
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

It is difficult to develop high-performance, durable oil-water separation coatings that do not contain fluorine compounds, especially in the textile industry where traditional fluorine compound-based coatings have environmental pollution and health risks.

Method used

Using polysiloxane (PDMS)-based materials, nanoparticles are added to improve surface roughness, and a low surface tension, molecular rough coating is formed through molecular structure design and synthesis technology.

Benefits of technology

It has achieved the development of an oil-water separation coating with a surface tension below 18 mN/m without using fluorine compounds, which has high washing resistance and durability, and is suitable for a variety of applications such as textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037933000031
    Figure 2025037933000031
  • Figure 2025037933000032
    Figure 2025037933000032
  • Figure 2025037933000033
    Figure 2025037933000033
Patent Text Reader

Abstract

To provide an oleophobic fabric based on nonfluorinated materials.SOLUTION: An oleophobic fabric comprises a fabric, and one or more oleophobic coating layers disposed on part or all of one or more exterior surfaces of the fabric. The oleophobic coating comprises one or more polymers, each polymer comprising one or more backbones and a plurality of pendant groups. The backbones are selected from among linear poly(dimethylsiloxane), branched poly(dimethylsiloxane), hydrocarbon polymer, polyacrylate, poly(methacrylate), poly(styrene), poly(vinylester), poly(allylether), polyester, polyurethane, polyurea, polyamide, polyimide, polysulfone, and any combination thereof. The pendant groups are covalently bonded to at least one backbone. Each pendant group is selected from the structures in the figure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Application No. 62 / 486,245, filed April 17, 2017, the disclosure of which is incorporated herein by reference. [Technical field]

[0002] The present disclosure relates generally to polymer-based oleophobic coatings. More specifically, the present disclosure relates to tree It concerns grease-based oleophobic coatings. [Background technology]

[0003] The textile industry is under intense pressure to remove all hazardous chemicals from their products and supply chain. The list of chemicals is long with fluorine-containing compounds. Per- and polyfluorinated materials are highly attractive in many industrial applications and consumer products (such as carpets, clothing, and upholstery) due to their resistance to both water and oil. Polyfluorinated compounds are resistant to degradation and persist in the environment. They bioaccumulate and some have been associated with adverse health effects, at least in laboratory animals.

[0004] Finding alternatives to fluorochemicals while maintaining the same level of performance and durability is not an easy task. Oleophobic coatings are useful in several consumer products and industrial applications, e.g., anti-wetting and self-cleaning. There are many examples of superhydrophobic coatings, but progress towards highly oleophobic coatings has been limited. Many superhydrophobic coatings have been found to be oleophilic. Furthermore, in contrast to the superhydrophobic state, oleophobicity can vary greatly depending on the type of oil. A superoleophobic surface (contact angle >150°) for a certain oil may be oleophilic for another oil with a lower surface tension.

[0005] The challenge in designing oleophobic coatings arises from fundamental limitations in materials. Typical surface tensions of hydrocarbon oils range from 20 to 36 mN / m, so according to Young's equation, the surface tension of a smooth oleophobic substrate is 20 mN / m. 2 It must be less than 100 nm. Specifically, the surface energy of olive oil is 32 mN / m, and depending on their type, the surface energy of vegetable oils is typically as low as 30 mN / m. Mineral oil, the first oil used in the AATCC® oleophobicity standard test (grade 1), has a surface energy of 31.5 mN / m. The requirement of low surface energy suggests that most commonly used materials are not inherently oleophobic. Only a few fluorinated materials can meet this prerequisite for oleophobicity. In fact, all so-called superoleophobic coatings developed to date use fluorine-based compounds with abundant -CF2 and -CF3 groups (e.g., PTFE, perfluorosilanes and perfluoropolymers). Considering the material limitations of intrinsic surface tension, essentially all previously developed high oleophobic coatings are based on low surface energy fluorinated materials.

[0006] Following the development of superhydrophobic materials, appropriate surface roughness can be introduced to enhance oleophobicity, for example, concave structures have been proposed to prepare oleophobic surfaces.

[0007] [Table 1] TIFF2025037933000044.tif244169[Table 1 continued] TIFF2025037933000045.tif224169

[0008] The use of these recessed structures has reduced the surface tension requirements of the substrate, but the fabrication of the recessed structures (typically by lithography together with chemical etching) tends to be difficult and expensive, especially for flexible substrates. For practical industrial applications, essentially all previously developed highly oleophobic coatings are still based on fluorinated materials, which have extremely low surface energies.

[0009] Very limited efforts have been made towards the development of oleophobic coatings using non-fluorinated materials. Typical PDMS has a surface energy of about 22-24 mN / m. Therefore, PDMS finishes do not generally provide efficient oleophobic coatings as their surface energy is not low enough. Furthermore, due to the different nature of the substrates, PDMS finishes can be problematic in terms of adhesion, uniformity, and mechanical properties.

[0010] A free-standing omniphobic membrane was prepared by microfluidic silicone oil emulsion templating. The membrane has uniform honeycomb-like microcavities with narrow openings that can be called concave structures. The membrane exhibited oleophobicity and flexibility without using fluorocarbons for surface modification and complex lithographic fabrication. However, microcavity membranes suffer from limited resistance to abrasion. The thin top layer of the narrow cavity openings wears off easily, and due to the loss of its concave structure, the membrane becomes less oleophobic or even oleophilic (although the membrane can still be superhydrophobic). To generate well-defined microcavity structures, careful solvent evaporation on a relatively uniform and flat substrate was used during emulsion templating. This is more challenging for rough substrates (e.g., upholstery fabrics) due to non-uniform solvent evaporation as a result of capillary effects. More importantly, the typical size of the microcavities is in the range of tens of microns, which is similar to or larger than the diameter of many common fibers, limiting microfluidic emulsion templating for textile finishing applications (not to mention processing scalability). A potential solution is to use the membrane as an add-on oleophobic film on the substrate. However, the feel and appearance of such an oleophobic surface may be compromised. Summary of the Invention

[0011] Based on the above, there is a continuing and unmet need to find alternatives to fluorinated compounds used in the textile and other industries while maintaining the same levels of performance and durability.

[0012] The present disclosure provides a method for determining whether a fluorine-containing polymer is capable of absorbing fluorine from 22 mJ / m2 disposed on some or all of a surface (e.g., some or all of an exterior surface) of a substrate (e.g., fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, etc.). 2 Less than (e.g., 22 mJ / m 2 The present disclosure also provides a method for making said layer and a use of said layer.

[0013] In one aspect, the present disclosure provides a method for treating a substrate comprising administering to a patient a radiation-resistant, ... 2 Less than (e.g., 22 mJ / m 2 The layer(s) may be a fluorine-free monolayer or a fluorine-free multilayer (e.g., a substantially fluorine-free monolayer or a substantially fluorine-free multilayer). The layer may comprise a plurality of individual layers.

[0014] A layer may be one or more tree For example, the resin may include a plurality of PDMS portions. For example, treeThe polymer comprises a crosslinkable group, including, but not limited to, acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof. The crosslinkable group is capable of interacting with the substrate (e.g., covalently and / or non-covalently bonded to the substrate) via one or more chemical bonds (e.g., covalent bonds, ionic bonds, hydrogen bonds, van der Waals interactions, or combinations thereof). In one example, the PDMS resin includes pendant branched PDMS resin and linear PDMS resin.

[0015] The layer can be disposed on some or all of the surface of the substrate (e.g., all of the surface, or all of the outer surface). The substrate can have a variety of sizes and shapes. The substrate can have a variety of compositions. The substrate can be a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, membrane, concrete, brick, etc. In one example where the substrate is a fabric, the fabric is a fabric that is naturally or modified to have superhydrophilic, hydrophilic, hydrophobic, or superhydrophobic properties.

[0016] In one aspect, the present disclosure provides a method for producing a layer as disclosed herein, the method comprising: tree It is based on coating with fat.

[0017] In various examples, 22 mJ / m2 disposed on some or all (e.g., all) of an exterior surface of a substrate (e.g., a substrate described herein, e.g., fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, etc.) 2 A layer (e.g., a molecularly rough layer) with a surface tension below 22 mJ / m 2 Curing with a surface tension of less than tree The method for forming the layer containing fat is as follows: Providing a substrate (e.g., fabric); A part or all of a surface (e.g., a part or all of an outer surface) of the substrate (e.g., a fabric) is tree Fat (e.g., pendant branch tree greasy or straight tree fats) (e.g., tree grease) (e.g., by dip coating or spray coating); The above tree curing (e.g., heat curing) the oil coating; In this case, 22 mJ / m 2 The following (e.g., 22 mJ / m 2 In one embodiment, a layer having a surface tension (eg, a molecularly rough layer) is formed on some or all of a surface (eg, some or all of an outer surface) of the substrate (eg, fabric).

[0018] In one aspect, the present disclosure provides an article of manufacture comprising one or more layers disclosed herein and / or one or more layers produced by the methods disclosed herein. [Brief description of the drawings]

[0019] For a fuller understanding of the nature and objectives of the present disclosure, reference should be made to the following detailed description taken in conjunction with the accompanying drawings.

[0020] FIG. 1 shows schematic diagrams of (a) fiber structures, (b) T structures, and (c) other common concave (reentrant) structures.

[0021] Figure 2 shows the pendant Kiju The synthesis diagram of fat is shown below. vinegar .

[0022] Figure 3 shows a linear tree The synthesis diagram of fat is shown below. Repeat Repeat unit (R2 SiO) can be 0 or greater than 1. In various examples, the number of repeating units, n, is from 10 to 400 (e.g., n is 50) and / or the value of m is from 1 to 50,000, from 1 to 25,000, or from 1 to 10,000.

[0023] FIG. 4 shows the deposition of one- and two-sided oleophobic coatings using composite nanofluids by dip coating (top) and spray coating (bottom).

[0024] Figure 5 shows SEM images of nanofluid modified oleophobic cotton fabric using dip-pad-dry-cure process: a) pristine oleophobic fabric, b) oleophobic fabric after 30 laundry washes.

[0025] Figure 6 shows a comparison of oil stain resistance of pristine cotton fabric (left) and nanofluid modified oleophobic cotton fabric (right). A drop of vegetable oil (colored with Oil Red O dye for clarity) was deposited on both fabrics.

[0026] Figure 7 shows an example of a branched pendant PDMS resin. The PDMS resin comprises a PDMS polymer having a PDMS backbone (main chain). The PDMS polymer can be formed using a multifunctional precursor (e.g., a bifunctional precursor having at least two acrylate groups). The PDMS resin can be colorless.

[0027] FIG. 8 shows an example of a PDMS resin. The PDMS resin is an example of a branched pendant PDMS resin. The PDMS resin has a PDMS skeleton and Contains siloxane bonds Branched PDMS polymers include those that can be formed using multifunctional precursors (e.g., precursors having at least three vinyl groups).

[0028] FIG. 9 shows the synthesis of oleophobic coated substrates by the graft-from method.

[0029] FIG. 10 shows SEM images of the fabric samples: (a) pristine fabric, (b) oleophobic fabric produced by surface-initiated atom transfer radical polymerization (graft-from atom-transfer radical poly / merization).

[0030] FIG. 11 shows photographs of oleophobic fabrics made from various materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Although the claimed subject matter has been described with respect to particular examples and / or embodiments, other embodiments, including embodiments that do not provide all of the advantages and features described herein, are also within the scope of the disclosure herein. Different structural, logical, and process steps may be made without departing from the scope of the disclosure herein.

[0032] Ranges of values ​​are disclosed herein. These ranges have lower and upper limits. Unless otherwise stated, the ranges include all values ​​up to the minimum value (either the lower or upper limit) and ranges between the values ​​in the stated ranges.

[0033] The present disclosure provides a method for determining whether a fluorine-containing polymer is capable of absorbing fluorine from 22 mJ / m2, disposed on some or all of a surface (e.g., some or all of an exterior surface) of a substrate (e.g., fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, etc.). 2 Less than (e.g., 22 mJ / m 2 The present invention provides a layer having a surface tension of less than 100 nm.

[0034] As used herein, the term "moiety" refers to a portion (substructure) or functional group of a molecule. For example, a moiety may be a precursor or treeA "moiety" is a part (substructure) or functional group of an oil. In various examples, a "moiety" refers to a chemical entity that has one end that can be covalently bonded to another chemical species (e.g., a group) or multiple (e.g., two) ends that can be covalently bonded to other chemical species. Examples of moieties include, but are not limited to, the following: The TIFF2025037933000046.tif21169 portion may be referred to as a group.

[0035] As used herein, unless otherwise indicated, the term "aliphatic" refers to a branched or unbranched hydrocarbon moiety / group that is saturated or, optionally, contains one or more degrees of unsaturation. Moieties that have a degree of unsaturation include, but are not limited to, alkenyl groups / moieties, alkynyl groups / moieties, and cycloaliphatic groups / moieties. For example, an aliphatic group can be any of the C1 to C6 40 (For example, C1~C 30 , C1~C 12 , C1~C 10 or C1-C5) (including all integer carbon numbers and ranges of carbon numbers therebetween) aliphatic groups / moieties (e.g., alkyl groups). Examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, butyl, isopropyl, tert-butyl, and the like. The aliphatic groups / moieties may be unsubstituted or substituted with one or more substituents. Examples of substituents include, but are not limited to, various substituents such as halogens (-F, -Cl, -Br, and -I), additional aliphatic groups (e.g., alkenes, alkynes), aryl groups, alkoxides, carboxylates, carboxylic acids, ether groups, hydroxyl groups, isocyanate groups, and the like, and combinations thereof.

[0036] In various examples, the present disclosure provides a layer that combines a low surface energy material with engineered surface roughness. The surface roughness can be engineered, for example, by exploiting the molecular structure of the base polymer or by stamping. Examples of molecular roughness include, but are not limited to, the use of copolymers containing branched or rigid segments, self-assembly of copolymers, microphase separation of polymer blends, and combinations thereof. resin Patterning can be achieved by utilizing techniques developed for microcontact printing and soft lithography.

[0037] In one aspect, the present disclosure provides a 22 mJ / m 2 Less than (e.g., 22 mJ / m 2 The layer(s) may be a fluorine-free monolayer or a fluorine-free multilayer (e.g., a substantially fluorine-free monolayer or a substantially fluorine-free multilayer). The layer may include multiple individual layers. In some examples, the layer is disposed on some or all of the substrate surface.

[0038] In some examples, fabrics, fibers, filaments, glass, ceramic, carbon, metal, wood, polymers, plastics, paper, membranes, concrete, bricks, etc., may have a thermal conductivity of 22 mJ / m2 disposed on some or all of their exterior surfaces (e.g., all of their exterior surfaces). 2 Less than (e.g., 22 mJ / m 2 The surface tension of the fluorine-free layer is preferably less than 100 nm.

[0039] The surface tension of the layer is 22, 21, 20, 19, or 18 mJ / m 2 For example, the layer is 12-22 mJ / m 2 , 12~20mJ / m 2 , or 12 to 18 mJ / m 2 has a surface tension of

[0040] The layers can have a variety of thicknesses. In various examples, the layer thickness is from a few nanometers to hundreds of microns. In various other examples, the layer thickness is from 10 nm to 300 microns, or from 50 nm to 100 microns.

[0041] A layer may be one or more tree For example, the resin may include multiple PDMS portions. For example, tree The polymer comprises a crosslinkable group, which may include, but is not limited to, one or more of acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof. The crosslinkable group is capable of interacting with the substrate (e.g., covalently and / or non-covalently bonded to the substrate) via one or more chemical bonds (e.g., covalent bonds, ionic bonds, hydrogen bonds, van der Waals interactions, or combinations thereof). In one example, the PDMS resin includes pendant branched PDMS resin and linear PDMS resin.

[0042] tree As fat, various P Rimar and / or Ko Polymers (eg, random copolymers). tree The resin may contain one or more polymer chains. The polymer chains may have a variety of structures. P Rimar and / or Ko In various examples, the polymer may include a combination of: tree The lipid comprises one or more poly(dimethylsiloxanes), each of which comprises one or more poly(dimethylsiloxane) moieties (e.g., one or more linear or branched poly(dimethylsiloxane) moieties). The moiety(s) may be, for example, a terminal moiety(s), such as a group(s). polymerindependently comprises one or more pendant groups having the structure: TIFF2025037933000047.tif22169In the formula, R is So Each R' is independently selected from an alkyl group and an -O-SiOR' group, and each R' in the -O-SiOR' group is independently selected from an alkyl group (e.g., a methyl group). tree The lipid comprises one or more polymers, each polymer comprising one or more backbones selected from linear or branched poly(dimethylsiloxanes), hydrocarbon polymers (e.g., polyethylene, polypropylene, polybutylene, etc.), polyacrylate polymers, poly(methacrylates), poly(styrenes), poly(vinyl esters), poly(aryl ethers), polyesters, polyurethanes, polyureas, polyamides, polyimides, polysulfones, and combinations thereof. In some cases, at least one pendant group has the structure: TIFF2025037933000048.tif22169R are each independently selected from an alkyl group and an -O-SiOR' group, where the R' group is an alkyl group, and the layer is disposed on some or all of the outer surface of the substrate. Ren , Ally Len, silyl moieties, and combinations thereof (e.g., -CH2- groups, -CH2CH2- groups, -CH2CH2CH2- groups, TIFF2025037933000049.tif18169-Si(CH3)2O-, -CH2O- group, -CH2CH3O- group, -CH2N- group, -CH2SO2- group; where n may be 0 to 40, including all integer values ​​and ranges therebetween. Examples of linking groups are described herein.

[0043] The above treeThe oil can include a polymer having a molecular weight of 140 g / mol or more (e.g., 400 g / mol or more, or 600 g / mol or more). To achieve a desired layer thickness, it may be desirable for the molecular weight of the polymer to be greater than 140 g / mol (e.g., greater than 400 g / mol, 600 g / mol, 1000 g / mol, 3000 g / mol, or 4000 g / mol). In some instances, the molecular weight is less than or equal to 10,000 g / mol.

[0044] tree Fat is a pendant branch tree Pendant branches may be tree The oil may comprise a plurality of aliphatic moieties and / or aliphatic groups (e.g., alkanediyl / alkenediyl moieties and / or alkanediyl / alkenediyl groups) and a plurality of pendant groups (e.g., Siloxane In one example, the backbone may include pendant branched groups. tree A silyl group is a resin formed by polymerization of one or more alkylsilyl compounds (which may be referred to as precursors (e.g., monomers)) that contain one or more aliphatic moieties and / or groups (e.g., alkanediyl / alkenediyl moieties and / or groups). For example, pendant branched tree The aliphatic resin is a resin formed by polymerization of a pendant-forming precursor (e.g., tris(trialkylsiloxy)silylalkylacrylate, etc.) and one or more crosslinking precursors (e.g., alkylacryloxyalkyltrialkoxysilane, etc.) that can crosslink with a substrate. The crosslinking precursor can be, for example, a comonomer having one or more hydroxyl, silanol, epoxy, carboxyl, aldehyde, amino, or isocyanate crosslinking groups, or combinations thereof. The individual aliphatic moieties and / or groups (e.g., alkanediyl / alkenediyl moieties and / or alkanediyl / alkenediyl groups) each independently have a C1 to C2 carbon atom. 40 (For example, C1~C 30 , C1~C 10, or C1-C5) (and all integer carbons and ranges therebetween). tree The resin is a resin formed by polymerization of tris(trimethylsiloxy)silylpropyl methacrylate and vinyltrimethoxysilane. See, for example, FIG. 2. The molar ratio of tris(trialkylsiloxy)silylalkyl acrylate to alkylacryloxyalkyltrialkoxysilane (e.g., tris(trimethylsiloxy)silylpropyl methacrylate to vinyltrimethoxysilane) is generally higher than 1. In one example, the ratio is 3-20.

[0045] Examples of crosslinkable moieties include, but are not limited to, the following, and combinations thereof: TIFF2025037933000050.tif54169In formula, R 3 is a hydrocarbon having 1 to 40 carbon atoms (including all integer values ​​of carbon and ranges therebetween) (e.g., methylene, ethylene, propylene, phenyl, diphenyl, naphthyl, etc.), n is 0 to 600 (including all values ​​and ranges therebetween), and X is a crosslinkable group, including, but not limited to, acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof. In various examples, the crosslinkable moieties become crosslinked moieties upon reaction of one or more crosslinkable groups (e.g., with crosslinkable groups on different polymer chains, the same polymer chain, substrate, or combinations thereof).

[0046] The PDMS resin may be a linear PDMS resin. A linear PDMS resin comprises a plurality of PDMS aliphatic moieties and / or groups (e.g., alkanediyl / alkenediyl moieties and / or groups) and, optionally, a plurality of pendant groups (e.g., SiloxaneThe PDMS resin can have a backbone containing a pendant group. For example, the PDMS resin can be a linear PDMS resin having a bond to the substrate (e.g., a reactive functional group terminated (e.g., amine terminated) PDMS, a resin formed by polymerization of a phenol (e.g., bisphenol A), and paraformaldehyde; a PDMS terminated with silanol, epoxy, carboxyl, aldehyde, isocyanate, thiol, vinyl, hydrogen, and hydroxyl groups). See, for example, FIG. 3. The aliphatic moieties and / or groups (e.g., alkanediyl / alkenediyl moieties and / or alkanediyl / alkenediyl groups) of the reactive functional group terminated PDMS and / or PDMS terminated with silanol, epoxy, carboxyl, aldehyde, isocyanate, thiol, vinyl, hydrogen, and hydroxyl groups, or combinations thereof, can each independently be any of C1 to C6. 40 Carbon atoms up to the number (e.g., C1 to C 30 , C1~C 10 , or C1-C5). In various examples, the repeating units of the PDMS polymer (e.g., R2 SiO- )(for example, (CH 3 ) 2 SiO or n in FIG. 3) is 0 or greater. In various examples, the number of repeat units can range from 0 to 400, including all integers and ranges of repeat units therebetween. In various examples, the number of repeat units in the PDMS polymer (e.g., m in FIG. 3) is at least 1. In various examples, the number of repeat units in the PDMS polymer (e.g., m in FIG. 3) is 1 to 50,000, 1 to 25,000, or 1 to 10,000. In various examples, the number of repeat units in the PDMS polymer (e.g., m in FIG. 3) is 5 to 50,000, 5 to 25,000, or 5 to 10,000. In various examples, m is 2,000. In various examples, n can be 0 to 400. In various examples, n is 50.

[0047] Any phenol can be used. Examples of suitable phenols include phenols containing at least two hydroxyl groups attached to one or more benzene rings and one or more short chain (e.g., C1-C5, or C1-C4) alkyl groups, or those having hydroxyl groups attached directly to one or more aromatic rings (e.g., hydroxylated C5-C 16 Examples of aromatic groups / moieties include, but are not limited to, hydroxylated naphthalene, hydroxylated pyrene, hydroxylated anthracene, etc. In one example, the phenol is bisphenol A.

[0048] The film can include nanoparticles (e.g., silica nanoparticles). The nanoparticles can be multifunctional nanoparticles. "Multifunctional nanoparticles" are defined as: tree It means that two or more functional groups are fixed on the nanoparticles (e.g., silanol groups on the nanoparticles) to improve compatibility with the oil and trimethylsiloxyl groups and to reduce the surface energy. The silica nanoparticles and the resin and / or the substrate may have covalent bonds and / or hydrogen bonds originating from the surface functional groups of these nanoparticles.

[0049] The nanoparticles can be metal, carbon, metal oxide, or semi-metal oxide (e.g., silica) nanoparticles. The nanoparticles can be surface functionalized with low surface energy groups (e.g., trimethylsiloxyl, methyl, t-butyl, benzoxazine, PDMS groups, etc.). The nanoparticles can have a variety of morphologies. In various examples, the nanoparticles are spheres, nanoplates, nanotubes, nanorods, nanowires, hierarchical structures produced by such nanoparticles, or combinations thereof. In one example, the layer includes a plurality of silica nanoparticles (e.g., Ludox HS silica, or other commercially available colloidal silica particles). The nanoparticles can be present in various amounts. In various examples, the nanoparticles are present in the layer at 0-95 wt % (including all integer weight % and ranges therebetween) based on the total weight of the layer. In one example, the nanoparticles are present in the layer at 20-40 wt %. The interaction between the silica nanoparticles and the resin or fiber / fiber can be in the form of covalent bonds and / or hydrogen bonds involving the surface functional groups of the nanoparticles.

[0050] The layer can be disposed on some or all of the exterior surface (or all of the exterior surface) of the substrate. The substrate can have a variety of sizes and shapes. The substrate can have a variety of compositions. Example substrate materials include, but are not limited to, fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, etc.

[0051] The substrate may be a fabric that is naturally or modified to have superhydrophilic, hydrophilic, hydrophobic or superhydrophobic properties. The fabric may be cotton, PET (polyethylene terephthalate), blends (e.g. cotton / PET blends), nylon, polyester, spandex, silk, wool, viscose, cellulosic fibers (e.g. TENCEL®), acrylic, polypropylene, or blends thereof. The fabric may be leather. The fabric may have a woven structure (e.g. plain weave, twill, satin, etc.), knitted structure (e.g. single jersey, double jersey, pique, mesh, etc.), or nonwoven structure (e.g. felt, fiber mat, membrane, film, leather, paper, etc.).

[0052] The substrate may include one or more concave (re-entrant) structures. Non-limiting examples of concave structures include fibrous structures (e.g., a non-limiting example of a fibrous structure as shown in FIG. 1a), T-shaped structures (e.g., a non-limiting example of a fibrous structure as shown in FIG. 1b), and derivative structures such as trapezoidal, matchstick, hoodoo / inverse opal, and mushroom structures (e.g., a non-limiting example of a derivative structure is shown in FIG. 1c). The substrate may include two or more different (e.g., different in terms of one or more properties; e.g., one or more dimensions, one or more types of concave structures, etc.) concave structures. The oleophobic behavior of a layer disposed on a substrate having these structures can be determined by the capillary length, the radius of the overhang R, the microstructure spacing D, and the local texture angle Ψ, as shown in FIG. 1, and compared to fibrous structures, the T-shaped structures may have high oleophobicity because they allow these parameters to be maximized simultaneously. In one example, the substrate does not include any recessed structures.

[0053] The layer can be disposed on a fabric having a superhydrophilic layer disposed on a portion of an outer surface of the fabric. Non-limiting examples of superhydrophilic layers are described in U.S. Patent Application Serial No. 14 / 122,535 (Wang et al., "Antifouling Ultrafiltration and RO / FO / Membranes"), the disclosures therein relating to superhydrophilic layers and methods of making superhydrophilic layers are incorporated herein by reference. In one example, the layer disclosed herein and the superhydrophilic layer are disposed on opposite sides of the fabric.

[0054] The superhydrophilic layer can include a plurality of superhydrophilic nanoparticles. The hydrophilic nanoparticles are silica nanoparticles that are surface-functionalized with alkylsiloxane-linker groups. In various examples, the superhydrophilic layer has a surface with a contact angle of less than 30 degrees, 25 degrees, 20 degrees, 15 degrees, 10 degrees, or 5 degrees. The superhydrophilic layer can be formed from nanoparticles made by methods known in the art.

[0055] The layer is oleophobic. The layer may be oleophobic and lipophobic. The layer may be lipophobic, oleophobic and hydrophobic. "Oleophobicity" refers to the physical property of a molecule that appears to be repelled from oil. The oleophobicity or oil repellency of the layer can be evaluated by AATCC® Test Method 118-2013. In various examples, the layer passes AATCC® Test Method 118-2013 for one or more oils (e.g., one or more oils set forth in AATCC® Test Method 118-2013). Lipophobicity, sometimes also called lipophobia, is a chemical property of a compound that means "fat rejection," literally "fear of fat." Lipophobic compounds are compounds that are not soluble in lipids or other non-polar solvents, e.g., water is lipophobic.

[0056] In one aspect, the present disclosure provides a method for producing a layer as disclosed herein. In various examples, the method includes depositing a layer on a substrate. treeIn various other cases, the graft-to method is based on coating the graft with lipids. tree Fat is also called the graft-from method.

[0057] In various examples, 22 mJ / m2 disposed on some or all (e.g., all) of an exterior surface of a substrate (e.g., a substrate described herein, e.g., fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, etc.) 2 A layer (e.g., a molecularly rough layer) with a surface tension below 22 mJ / m 2 Less than curing tree The method for forming the layer containing fat is as follows: Providing a substrate (e.g., fabric); A part or all of a surface (e.g., a part or all of an outer surface) of the substrate (e.g., a fabric) is tree Fat (e.g., pendant branch tree greasy or straight tree fats) (e.g., tree grease) (e.g., by dip coating or spray coating); The above tree curing (e.g., heat curing) the oil coating; In this case, 22 mJ / m 2 The following (e.g., 22 mJ / m 2 In one embodiment, a layer having a surface tension (eg, a molecularly rough layer) is formed on some or all of a surface (eg, some or all of an outer surface) of the substrate (eg, fabric).

[0058] Curing may result in crosslinking (e.g., formation of one or more covalent bonds) between one or more polymer chains of the layer and / or between one or more polymer chains and the substrate. Crosslinking may form crosslinked moieties (e.g., from reaction of one or more crosslinkable moieties).

[0059] A variety of coating methods can be used, including, but not limited to, spray coating, dip coating, floating knife coating, direct roll coating, padding, calendar coating, foam coating, and painting.

[0060] tree Fat is nanoparticles, tree The nanoparticles may be (e.g., include) a mixture of a resin, a fat, and optionally a solvent. Such a resin may be referred to as a "composite nanofluid." In various examples, a substrate is coated with the composite nanofluid. The nanoparticles are believed to increase the surface roughness of the layer. Additionally, the nanoparticles may increase the mechanical durability and strength of the layer (e.g., a fabric having a layer disposed on at least a portion or all (e.g., all) of an outer surface of the fabric).

[0061] The layer(s) can be formed by in situ polymerization. For example, the layer grows via polymerization initiated from a substrate (e.g., one or more groups disposed on a substrate). For example, the polymerization is a radical polymerization. In various examples, the radical polymerization is a living polymerization, such as, for example, atom transfer radical polymerization (ATRP).

[0062] An example of in situ polymerization is S A substrate having a plurality of functional groups capable of initiating polymerization of a siloxane precursor (e.g., a substrate having one or more of the following groups disposed on its surface): etc. , or a combination thereof), TIFF2025037933000051.tif35169 contacting the reaction mixture with one or more S and (i) or (ii) below, wherein the initiator layer and / or the initiator layer are disposed on the surface of the substrate. Polymers with siloxane bonds A layer containing (i) one or more radical initiators (e.g., a halide initiator such as TIFF2025037933000052.tif26169; an azo radical initiator such as azobisisobutyronitrile (AIBN); a peroxide such as benzoyl peroxide; an alkoxyamine such as 2,2,6,6-tetramethylpiperidin-1-yl)oxyl; a chain transfer agent such as cyanomethyl[3-(trimethoxysilyl)propyl]trithiocarbonate, or the like, or a combination thereof; (ii) one or more metal catalysts (e.g., Cu(I), Cu(II), Fe(II), Fe(III), Co(II), and the like, and combinations thereof) and one or more amines (e.g., diethylenetriamine, triethylenetetraamine, N,N-bis(2-pyridylmethyl)amine, tris[2-aminoethyl]amine, 1,4,8,11-tetraazacyclotetradecane, 2,2'-bipyridine, 4,4'-di(5-nonyl)-2,2'-bipyridine, N,N,N',N'-tetramethylethylenediamine, N-propyl(2-pyridyl)methanimine, 2,2':6',2''-terpyridine, 4,4',4''-tris(5-nonyl)- one or more activating agents including 2,2':6',2''-terpyridine, N,N,N',N'',N''-pentamethyldiethylenetriamine, N,N-bis(2-pyridylmethyl)octylamine, 1,1,4,7,10,10-hexamethyltriethylenetetraamine, tris[2-(dimethylamino)ethyl]amine, tris[(2-pyridyl)methyl]amine, 1,4,8,11-tetraaza-1,4,8,11-tetramethylcyclotetradecane, N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine, and the like, combinations thereof.

[0063] The substrate may be pretreated prior to coating. In one example, nanoparticles are disposed and / or grown on some or all (e.g., all) of the outer surface of the substrate. In various examples, the method includes forming a layer including a plurality of nanoparticles on some or all (e.g., all) of the outer surface of the fabric prior to forming the layer disclosed herein. In various examples, the forming includes coating (e.g., by dip coating or spray coating) some or all of the outer surface of the fabric with a silica sol (e.g., a silica sol formed by hydrolyzing (e.g., in an alcohol / water solution) (e.g., under alkaline conditions) one or more tetraalkoxysilanes) and drying the coated fabric. Combinations of tetraalkoxysilanes can also be used. Examples of tetraalkoxysilanes include, but are not limited to, tetramethoxysilane, tetraethoxysilane, tetrapropylorthosilicate, tetrabutylorthosilicate, and combinations thereof. Silica sol can also be formed by acidifying sodium silicate.

[0064] In one example, the method including pre-treating the substrate further includes contacting the dried fabric with silica nanoparticles (eg, a suspension of silica nanoparticles).

[0065] The substrate may be cleaned prior to use. In one example, the substrate (e.g., a fabric or a fabric having a plurality of nanoparticles disposed thereon) is cleaned (e.g., plasma cleaned, oxidized, rinsed with a solvent such as water and / or other solvents (e.g., organic solvents, etc.)) prior to coating with the silica sol.

[0066] The coating and curing process can be repeated as many times as desired. It may be desirable to repeat the coating and curing process to obtain a layer having a desired thickness. In various examples, the coating and curing process is repeated from 1 to 20 times (including all integer numbers therebetween).

[0067] In various examples, the method further includes forming additional surface roughness on the film, which can be formed, for example, by nanofabrication, electrospinning, forced spinning, extrusion, mechanical stamping, abrasion, etching, or a combination thereof.

[0068] In one aspect, the present disclosure provides an article of manufacture comprising one or more layers disclosed herein and / or one or more layers made by the methods disclosed herein.

[0069] Examples of articles of manufacture include, but are not limited to, fabric, clothing such as shirts, jackets, pants, hats, ties, coats, shoes, etc. (e.g., clothing such as children's clothing, adult clothing, industrial work clothing, etc.), food packaging, eyeglasses, displays (e.g., touch screens), scanners (e.g., fingerprint scanners), airplane coatings, sporting equipment (e.g., tents, uniforms, etc.), building materials (e.g., windows), windshields.

[0070] The manufactured goods may be used in a variety of industries, including, but not limited to, aerospace, automotive, building and construction, food processing, and electronics.

[0071] The method steps described in the various embodiments and examples disclosed herein are sufficient to carry out the methods disclosed herein. Thus, in various examples, the method consists essentially of a combination of the method steps disclosed herein. In various other examples, the method consists solely of such steps.

[0072] The following statements are based on the layers disclosed herein (e.g., 22 mJ / m 2 Surface tension below (e.g., 12-22 mJ / m 2) a molecularly rough layer having a surface roughness of at least one of the surfaces of the substrate, methods disclosed herein (e.g., methods of making a layer disclosed herein), and articles of manufacture disclosed herein (e.g., articles of manufacture including one or more layers disclosed herein) are provided. Statement 1. 22 mJ / m2 disposed on some or all of the outer surface of the substrate (e.g., all of the outer surface) 2 (For example, 12 to 22 mJ / m 2 ) a layer (e.g., a molecularly rough layer) disclosed herein having a surface tension of less than or equal to 100 nm. Statement 2. 1 or more tree A layer (e.g., a layer disposed on a substrate) comprising an oil, tree The fat comprises (i) and / or (ii) of: i) one or more poly(dimethylsiloxanes), each poly(dimethylsiloxane) containing one or more poly(dimethylsiloxane) moieties (e.g., linear or branched poly(dimethylsiloxane) moieties(s); and Optionally, the poly(dimethylsiloxane)(s) independently comprise one or more pendant groups having the following structure: TIFF2025037933000053.tif22169Here, the linking group is an alkyl group. Ren , Ally Len, silyl moieties, and combinations thereof (e.g., -CH2- groups, -CH2CH2- groups, -CH2CH2CH2- groups, TIFF2025037933000054.tif18169-Si(CH3)2O-, -CHO- group, -CH2CH3O- group, -CH2N- group, -CH2SO2- group; where n may be 0 to 40, including all integer values ​​and ranges therebetween, and R is independently selected from an alkyl group and a -O-SiOR' group among said poly(dimethylsiloxane)(s), and R' is independently selected from an alkyl group (e.g., a methyl group) among the -O-SiOR' group(s); ii) one or more polymers, each polymer comprising one or more backbones selected from linear or branched poly(dimethylsiloxanes), hydrocarbon polymers (e.g., polyethylene, polypropylene, polybutylene, etc.), polyacrylate polymers, poly(methacrylates), poly(styrenes), poly(vinyl esters), poly(aryl ethers), polyesters, polyurethanes, polyureas, polyamides, polyimides, polysulfones, and combinations thereof; and optionally At least one pendant group having the structure: TIFF2025037933000055.tif22169The linking group is an alkyl group. Ren , Ant Ren, silyl moieties, and combinations thereof (e.g., -CH2- groups, -CH2CH2- groups, -CH2CH2CH2- groups, TIFF2025037933000056.tif18169-Si(CH3)2O-, -CH2O- group, -CH2CH3O- group, -CH2N- group, -CH2SO2- group; where n can be 0 to 40, including all integer values ​​and ranges therebetween, and each R is independently selected from an alkyl group and a -O-SiOR' group, where R' group is an -alkyl group. In this case, the layer is disposed on a part or the entire surface of the substrate. Statement 3. The layer of statement 2, wherein the one or more poly(dimethylsiloxane)s comprise linear poly(dimethylsiloxane) moieties(s), branched poly(dimethylsiloxane) moieties(s), or a combination thereof. Statement 4. Any one of the foregoing statements, wherein the PDMS resin is a linear PDMS resin (e.g., a PDMS resin having a bonding group to a substrate) (e.g., amine-terminated PDMS, a phenol having a hydroxyl group bonded to a benzene ring and a single-chain (<C5) alkyl group, or a phenol having a hydroxyl group directly bonded to an aromatic ring (e.g., bisphenol A), and a resin formed by polymerization of paraformaldehyde; PDMS terminated with silanol, epoxy, carboxyl, aldehyde, isocyanate, thiol, vinyl, hydrogen and hydroxyl groups, or a combination thereof). For example, see Figure 3. For example, the alkyl portion of the amine-terminated PDMS precursor, or PDMS terminated with silanol, epoxy, carboxyl, aldehyde, isocyanate, thiol, vinyl, hydrogen, hydroxyl groups, or a combination thereof, are each independently from C1 to C 40 (including all integer values of carbon and ranges therebetween) (e.g., C1~C 30 , C1~C 10 , or C1~C5). Statement 5. Any one of the layers of Statements 2 to 4, wherein the one or more poly(dimethylsiloxane) are as follows, TIFF2025037933000057.tif37169 wherein R 2 are each independently selected from H, a hydrocarbon group having 1 to 40 carbon atoms, or an -O-SiOR' group, where the R' group is an alkyl group (e.g., C1~C 40 , C1~C 30 , C1~C 10 , or C1~C5); n is from 0 to 400, and m is from 1 to 50,000. Statement 6. Said one or more resin of at least one has one or more crosslinkable groups, any one of the layers of Statements 2 to 5. Statement 7. 7. The layer of any one of statements 2-6, wherein the crosslinkable groups are selected from acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof. Statement 8. Any one of the layers of claims 2 to 7, resin is formed by polymerization of one or more tris(trialkylsiloxy)silyl vinyl compounds (e.g., tris(trialkylsiloxy)silyl alkyl acrylates, such as tris(trialkylsiloxy)silyl methacrylates, etc.) and trimethoxysilane vinyl compounds (e.g., alkyl acryloxy alkoxy trimethoxy silanes, etc.), wherein the alkyl moieties (e.g., alkyl moiety(s) and / or alkyl group(s)) are each independently selected from the group consisting of C1 to C6 40 It is an alkyl moiety. See, for example, Figure 2. Statement 9. The above-mentioned compounds derived from these precursors tree Fat or the above tree Any one of statements 2 to 8, wherein the molar ratio of tris(trialkylsiloxy)silylalkylacrylate to vinylsilane (e.g., the molar ratio of tris(trimethylsiloxyl)silylpropyl methacrylate to vinyltrimethoxysilane) used to prepare the interfacial portion is greater than 1 (e.g., 3 to 20). Statement 10. The alkyl moieties are each independently C1 to C 30 , C1~C 10 The layer of any one of statements 2 to 9, wherein the alkyl moiety is a C1 to C5 alkyl moiety. Statement 11. the pendant groups are selected from: and optionally, the pendant groups are linked to the poly(dimethylsiloxane) resin or The above 13. Any one of the layers of statements 2 to 10, covalently attached to the backbone. statement 12 12. The layer of any one of claims 2 to 11, wherein the poly(dimethylsiloxane) has the following structure: TIFF2025037933000059.tif13169In the formula, n is 0 to 600, m is 0 to 3, and X is a crosslinkable group, including but not limited to: acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof. Statement 13. R2 of the one or more poly(dimethylsiloxane) moieties or the linear or branched poly(dimethylsiloxane)(s) backbone SiO (for example , (CH 3 ) 2 SiO ) Any one of the layers of statements 2 to 12, wherein the number of repeating units is 0 to 400. Statement 14. The repeating unit of the PDMS (e.g., (CH 3 ) 2 SiO 14. The layer of any one of claims 2-13, wherein the number of aryl groups is greater than 2, preferably 10-400. Besides the graft-to method (e.g., dip coating, spray coating, emulsion / foam coating, etc.), the coating can be applied to the substrate by the graft-from method (e.g., as shown in FIG. 9). The initiator may be a reversibly deactivated radical generator, such as a compound containing one or more organic halogenated moieties (e.g., an alkyl halide), or one or more alkoxyamine moieties, or a suitable chain transfer agent, such as one or more thiocarbonylthio moieties. The monomer may be one or more alkylsilyl compounds containing one or more aliphatic moieties and / or aliphatic groups. Statement 15. 15. Any one of statements 2 to 14, wherein the layer is cured. Statement 16. 16. The layer of any one of claims 2 to 15, wherein the layer further comprises: treeBetween the two polymer chains of fat ( tree and / or having at least one crosslink (e.g., more than 2, more than 5, more than 10 crosslinks, or more than 25 crosslinks) between the polymer chains (which may be the same or different polymer chains of the same polymer chain); tree Fat polymer chain ( tree The polymer may have at least one crosslink (e.g., more than 2, more than 5, more than 10, or more than 25 crosslinks) between the polymer chain (which may be the same or a different polymer chain) and the substrate. Statement 17. 17. The layer of any one of statements 2-16, wherein the layer further comprises one or more cross-linking moieties selected from the following: TIFF2025037933000060.tif91169In formula, R 3 is a hydrocarbon group having 1 to 40 carbon atoms (including all integer values ​​of carbon and ranges therebetween) (e.g., methylene, ethylene, propylene, phenyl, biphenyl, naphthyl, etc.), and n is 0 to 600 (including all values ​​and ranges therebetween). Statement 18. 18. The layer of any one of statements 2-17, wherein the layer comprises a plurality of nanoparticles disclosed herein (e.g., silica nanoparticles such as Ludox HS silica, and other commercially available colloidal silica particles). Statement 19. 20. The layer of claim 18, wherein the plurality of nanoparticles are selected from the group consisting of silica nanoparticles. Statement 20. 20. The layer of claim 18 or 19, wherein the weight percentage of the nanoparticles is 1-98 wt % (e.g., 1-95 wt % or 1-50 wt %), based on the total weight of the layer. Statement 21. 21. The layer according to any one of statements 18 to 20, wherein the weight percentage of the nanoparticles is 0 to 95 wt%, preferably 20 to 40 wt%. Statement 22. The layer according to any one of the preceding statements, wherein the substrate is a substrate disclosed herein. Statement 23. The layer of any one of the preceding statements, wherein the thickness of the layer is from 10 nm to 300 microns (e.g., from 50 nm to 100 microns). Statement 24. The layer of any one of the preceding statements, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, or the like. Statement 25. 25. The layer of claim 24, wherein the fabric is selected from cotton, PET, cotton / PET blends, nylon, polyester, spandex, silk, wool, viscose, cellulosic fibers, acrylic, polypropylene, or blends thereof (e.g., a blend of two or more yarns capable of forming a fabric, including cotton, PET, cotton / PET blends, nylon, polyester, spandex, silk, wool, viscose, cellulosic fibers, acrylic, polypropylene yarns as fabric materials), leather, and combinations thereof. Statement 26. 26. The layer of claim 25, wherein the substrate is a fabric having a superhydrophilic layer disposed on a portion of an outer surface of the fabric. Statement 27. The layer has a density of 22 mJ / m 2 27. The layer of any one of claims 2 to 26, having a surface tension of: Statement 28. 22mJ / m 2 28. The layer of any one of claims 2 to 27, wherein the layer having a surface tension of: Statement 29. The layer according to any one of the preceding statements, wherein the substrate and / or layer is fluorine-free. Statement 30. The layer of any one of the preceding statements, wherein the layer passes AATCC® Test Method 118-2013 for one or more oils (e.g., one or more oils set forth in AATCC® Test Method 118-2013). Statement 31. A layer (e.g., a molecularly roughened layer) disclosed herein (e.g., 22 mJ / m 2 ) disposed on some or all (e.g., all) of an outer surface of a substrate (e.g., fabric) 2 (e.g., a layer having a surface tension of less than tree A method for forming a layer (a layer containing fat), comprising the steps of: Providing a substrate (e.g., fabric); A part or all of the outer surface of the substrate (for example, the entire outer surface) is tree Fat (e.g., pendant branch tree greasy or straight tree fats) (e.g., tree The fat, for example, according to any one of claims 4 to 13 tree coating with nanofluids (e.g., by spray coating, dip coating, floating knife coating, direct roll coating, padding, calendar coating, or foam coating); The above tree Curing (e.g., heat curing) the oil coating or coating formed from the composite nanofluid. wherein the layer (e.g., a molecularly roughened layer) disclosed herein (e.g., 22 mJ / m 2 A layer having a surface tension less than about 100 nm is formed on some or all of the outer surface (eg, all of the outer surface) of the substrate. Statement 32. 1. A method of forming a layer as disclosed herein disposed on some or all of an exterior surface of a substrate, comprising: A part or all of the outer surface of the substrate is tree Coating with a grease or composite nanofluid; and The above tree Heating and curing the coating at the temperature of the oil coating or the coating formed from the composite nanofluid (e.g., maintaining the coating at a temperature of -30°C to 200°C, such as 20°C to 160°C, for example, for 1 second to 2 weeks). wherein a layer as disclosed herein is formed on some or all of the exterior surface of the substrate. Statement 33. 33. The method according to claim 31 or 32, The above tree The fat comprises (i) and / or (ii) of: i) one or more poly(dimethylsiloxane) resins comprising one or more poly(dimethylsiloxane) moieties (e.g., linear or branched poly(dimethylsiloxane) moieties(s); wherein, optionally, the poly(dimethylsiloxane) resin comprises one or more pendant groups having the structure: TIFF2025037933000061.tif22169R is independently selected from an alkyl group and a -O-SiOR' group among said poly(dimethylsiloxane)(s), and R' is independently selected from an alkyl group (e.g., a methyl group) among the -O-SiOR' group(s); ii) one or more polymers, a backbone selected from linear or branched poly(dimethylsiloxane), a hydrocarbon polymer (e.g., polyethylene, polypropylene, polybutylene, etc.), a polyacrylate polymer, a poly(methacrylate), a poly(styrene), a poly(vinyl ester), a poly(aryl ether), a polyester, a polyurethane, a polyurea, a polyamide, a polyimide, a polysulfone, and combinations thereof; and at least one pendant group having the structure TIFF2025037933000062.tif22169 where each R is independently selected from an alkyl group and a -O-SiOR' group, and the R' group is an alkyl group. Statement 34. The composite nanofluid comprises: tree 34. The method of any one of claims 31 to 33, comprising a lipid, one or more nanoparticles, and optionally a solvent (e.g., toluene, xylene, a hydrocarbon having 4 to 16 carbon atoms (e.g., hexane, etc.), chloroform, tetrahydrofuran, and combinations thereof). Statement 35. 35. The method of any one of claims 31 to 34, wherein the substrate is a substrate disclosed herein. Statement 36. 36. The method of any one of claims 31 to 35, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, or the like. Statement 37. The substrate has a superhydrophilic layer disposed on all or at least a portion of the outer surface of the fabric (e.g., a layer disclosed herein (e.g., 22 mJ / m 2 37. The method of any one of claims 31 to 36, wherein the fabric has a superhydrophilic layer disposed on a surface of the fabric opposite to the surface on which the layer having a surface tension below 100 nm is formed. Statement 38. 38. The method of any one of claims 31 to 37, wherein the substrate is fluorine-free. Statement 39. The method of any one of claims 31-38, wherein the forming comprises coating (e.g., by dip coating or spray coating) some or all of the exterior surface of the substrate with a silica sol (e.g., a silica sol formed by hydrolyzing (e.g., in an alcohol / water solution) (e.g., under alkaline conditions) one or more tetraalkoxysilanes) and drying the coated fabric. Examples of tetraalkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetrapropylorthosilicate, tetrabutylorthosilicate, and combinations thereof. The silica sol can also be formed by acidifying sodium silicate. Statement 40. 40. The method of claim 39, wherein the coating is spray coating, dip coating, floating knife coating, direct roll coating, padding, calendar coating, foam coating, or a combination thereof. Statement 41. 41. The method of any one of claims 31-40, further comprising contacting the dried substrate with nanoparticles (e.g., silica nanoparticles, such as a suspension of silica nanoparticles). Statement 42. The method of any one of statements 31-41, further comprising pretreating the substrate. Statement 43. The layers disclosed herein (e.g., 22 mJ / m 2 43. The method of any one of claims 31-42, comprising forming a layer on some or all of the exterior surface (e.g., all of the exterior surface) of the substrate prior to forming a layer on the substrate (e.g., a layer having a surface tension of less than 100 nm). Statement 44. 44. The method of any one of claims 31 to 43, wherein the pretreatment is a chemical treatment (e.g., plasma treatment, solvent washing, oxidation treatment, hydrolysis treatment, etc., and combinations thereof), a physical treatment (e.g., polishing treatment, etc.), a primer treatment (e.g., using a sol-like primer comprising one or more sol-gel precursors and an epoxide primer, which contains one or more of acrylate groups, methacrylate groups, allyl groups, vinyl groups, thiol groups, hydroxyl groups, silanol groups, carboxylic acid groups, carboxylate groups, aldehyde groups, amine groups, isocyanate groups, azide groups, epoxy groups, halide groups, hydrogen groups, etc., and combinations thereof), or a combination thereof. Statement 45. 45. The method of any one of claims 31-44, wherein the pretreatment comprises coating a portion or all of the exterior surface of the substrate with a sol of a non-metal oxide (e.g., silicon oxide, etc.), a metal oxide (e.g., aluminum oxide, titanium oxide, iron oxide, copper oxide, etc., and combinations thereof), or a combination thereof (e.g., the layer comprises a non-metal oxide, a metal oxide, or a combination thereof). For example, the coated substrate (e.g., a silica sol coated substrate, etc.) may comprise one or more functional groups, such as, for example, acrylate groups, methacrylate groups, allyl groups, vinyl groups, thiol groups, hydroxyl groups, silanol groups, carboxylic acid groups, carboxylate groups, aldehyde groups, amine groups, isocyanate groups, azide groups, alkyne groups, epoxy groups, halide groups, hydrogen groups, and combinations thereof, which may enhance crosslink density between the coated substrate and the layer. Statement 46. 46. ​​The method of any one of claims 31 to 45, wherein the substrate is cleaned (eg, plasma cleaned) prior to coating with the silica sol. Statement 47. 47. The method of any one of claims 31-46, wherein the substrate has a plurality of nanoparticles disposed thereon. Statement 48. The method of any one of claims 31-47, further comprising contacting the substrate (e.g., having a dried and / or cured layer) with silica nanoparticles. Some or all of the nanoparticles (e.g., silica nanoparticles, etc.) may be covalently bonded to the substrate, bonded and / or aggregated with other nanoparticles, or combinations thereof. In various examples, some or all of the nanoparticles form a concave structure. Statement 49. The method of any one of claims 31 to 48, wherein the coating and curing (e.g., the coating and curing method of any one of claims 8 to 16) is repeated a desired number of times (e.g., 1 to 20 times). Statement 50. 50. The method of any one of claims 31-49, further comprising providing additional surface roughness to the layer (e.g., by nanofabrication, electrospinning, force spinning, extrusion, mechanical stamping, abrasion, etching, or a combination thereof). Statement 51. disposed on a portion or all of the outer surface of the substrate; resin A method (e.g., an in situ method) for forming a layer (e.g., a layer disclosed herein) comprising: S A substrate having a plurality of functional groups capable of initiating polymerization of a siloxane precursor (e.g., having one or more of the groups shown below disposed on its surface, or a combination thereof) is TIFF2025037933000063.tif32169 contacting the reaction mixture with one or more S and (i) or (ii) below, wherein the substrate is disposed on the surface of the substrate. Layer (polymer having siloxane bonds) Layer containing ) is formed (i) one or more radical initiators (e.g., a halide initiator such as TIFF2025037933000064.tif27169; an azo radical initiator such as azobisisobutyronitrile (AIBN); a peroxide such as benzoyl peroxide; an alkoxyamine such as 2,2,6,6-tetramethylpiperidin-1-yl)oxyl; a chain transfer agent such as cyanomethyl[3-(trimethoxysilyl)propyl]trithiocarbonate, or the like, or a combination thereof; (ii) one or more metal catalysts (e.g., Cu(I), Cu(II), Fe(II), Fe(III), Co(II), and the like, and combinations thereof) and one or more amines (e.g., diethylenetriamine, triethylenetetraamine, N,N-bis(2-pyridylmethyl)amine, tris[2-aminoethyl]amine, 1,4,8,11-tetraazacyclotetradecane, 2,2'-bipyridine, 4,4'-di(5-nonyl)-2,2'-bipyridine, N,N,N',N'-tetramethylethylenediamine, N-propyl(2-pyridyl)methanimine, 2,2':6',2''-terpyridine, 4,4',4''-tris(5-nonyl)- one or more activating agents including 2,2':6',2''-terpyridine, N,N,N',N'',N''-pentamethyldiethylenetriamine, N,N-bis(2-pyridylmethyl)octylamine, 1,1,4,7,10,10-hexamethyltriethylenetetraamine, tris[2-(dimethylamino)ethyl]amine, tris[(2-pyridyl)methyl]amine, 1,4,8,11-tetraaza-1,4,8,11-tetramethylcyclotetradecane, N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine, and the like, combinations thereof. Statement 52. 52. The method of claim 51, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, or the like. Statement 53. 53. The method of any one of claims 51 to 52, wherein the substrate has a plurality of nanoparticles disposed thereon. Statement 54. 54. The method of any one of claims 51 to 53, wherein the substrate is fluorine-free. Statement 55. 55. The method of any one of statements 51-54, further comprising pre-treatment of the substrate. Statement 56. 56. The method of any one of claims 51 to 55, wherein the pretreatment is a chemical treatment (e.g., plasma treatment, solvent washing, oxidation treatment, hydrolysis treatment, etc., and combinations thereof), a physical treatment (e.g., polishing treatment, etc.), a primer treatment (e.g., using a sol-like primer comprising one or more sol-gel precursors and an epoxide primer; which contains one or more of acrylate groups, methacrylate groups, allyl groups, vinyl groups, thiol groups, hydroxyl groups, silanol groups, carboxylic acid groups, carboxylate groups, aldehyde groups, amine groups, isocyanate groups, azide groups, alkyne groups, epoxy groups, halide groups, hydrogen groups, etc., and combinations thereof), or a combination thereof. Statement 57. 57. The method of any one of claims 51-56, wherein the pretreatment comprises coating a portion or all of the exterior surface of the substrate with a sol of a non-metal oxide (e.g., silicon oxide, etc.), a metal oxide (e.g., aluminum oxide, titanium oxide, iron oxide, copper oxide, etc., and combinations thereof), or a combination thereof (e.g., the layer comprises a non-metal oxide, a metal oxide, or a combination thereof). For example, the coated substrate (e.g., a silica sol coated substrate, etc.) may comprise one or more functional groups, such as, for example, acrylate groups, methacrylate groups, allyl groups, vinyl groups, thiol groups, hydroxyl groups, silanol groups, carboxylic acid groups, carboxylate groups, aldehyde groups, amine groups, isocyanate groups, azide groups, alkyne groups, epoxy groups, halide groups, hydrogen groups, and combinations thereof, which may enhance crosslink density between the coated substrate and the layer. Statement 58. Furthermore, the substrate ( S Roxanne Polymers with bonds 58. The method of any one of claims 51 to 57, comprising contacting a silica nanoparticle (which may have a layer) with silica nanoparticles. Some or all of the nanoparticles (e.g., silica nanoparticles, etc.) may be covalently bonded to the substrate, bonded and / or aggregated with other nanoparticles, or combinations thereof. In various examples, some or all of the nanoparticles form a concave structure. Statement 59. 59. The method of any one of statements 51 to 58, wherein the contact is repeated 1 to 20 times. Statement 60. 60. The method of any one of claims 51 to 59, further comprising providing additional surface roughness to the layer. Statement 61. 61. The method of any one of statements 51-60, wherein additional surface roughness is applied to the layer by nanofabrication, electrospinning, force spinning, extrusion, mechanical stamping, abrasion, etching, or a combination thereof. Statement 62. An article of manufacture comprising one or more layers disclosed herein, for example, one or more layers formed by the method described in any one of statements 31-61. Statement 63. A layer (e.g., a molecularly roughened layer) (e.g., 22 mJ / m) disclosed herein disposed on some or all (e.g., all) of the outer surface of a substrate disclosed herein. 2 31. An article of manufacture comprising one or more fabrics having a surface tension of less than 100 nm (e.g., a layer described in any one of statements 1-30, or a layer made by the method described in any one of statements 31-61). Statement 64. 64. The article of manufacture of claim 62 or 63, wherein the article of manufacture is a product described herein. statement 65 The article of manufacture of any one of statements 62-64, wherein the article of manufacture is a fabric, a garment, a food packaging, eyeglasses, a display, a scanner, an airplane coating, a sporting goods, a building material, a window, a windshield, a corrosion resistant coating, an anti-icing coating, or a cooler (e.g., a condenser for cooling a vapor, such as water vapor), a light (e.g., a traffic light, a headlight, a lamp, etc.).

[0073] The following examples are presented to illustrate the present disclosure and are not intended to be limiting in any manner. [Example 1]

[0074] This example describes a film of the present disclosure.

[0075] Methodology and Results: We are molecularly coarse table A fluorine-free oleophobic coating based on a surface is described. In some designs, the surface roughness is achieved by the addition of nanoparticles. A surface energy of 18 mN / m or less has been demonstrated, resulting in an oleophobic surface up to grade 3 (based on AATCC® 118). The coating is sufficiently robust to withstand repeated wash / rinse cycles (30 cycles) and treatment with various organic solvents (e.g., acetone, ethanol, etc.).

[0076] tree Synthesis of fat

[0077] Two different tree Fat synthesis:

[0078] Pendant branch tree Fat (schematically shown in Figure 2): Tris(trimethylsiloxy)silylpropyl acrylate (10 mmol), vinyltrimethoxysilane (1 mmol) and azobisisobutyronitrile (0.1 mmol) were dissolved in dry xylene (20 mL) at room temperature and purged with nitrogen for 5 minutes. The monomer solution was then heated to 65° C. and maintained at that temperature for 24 hours.

[0079] Linear PDMS resin (Figure 3): Amine-terminated PDMS (10 mmol), bisphenol A (10 mmol) and paraformaldehyde (40 mmol) were dissolved in 150 mL of chloroform in a 500 mL round-bottom flask. The mixture was heated under reflux for 6 h to give a clear, pale yellow solution. After removing the solvent under vacuum, the viscous residue was dissolved in dichloromethane and washed five times with saturated aqueous NaHCO3 and distilled water. After drying the washing solution under vacuum, a viscous, pale yellow liquid product was obtained.

[0080] Fabric pretreatment

[0081] Cotton or PET fabrics of 1 cm × 1 cm were washed with ethanol and dried in an oven at 80 °C for 10 min. Separately, silica sol was prepared by alkaline hydrolysis of tetraethoxysilane (10 mmol) in an ethanol / water solution (75 mL, 80% v / v) in the presence of ammonium hydroxide (2.75 mL). The fabrics were plasma cleaned, then immersed in the sol for 5 min and dried at room temperature. This process was repeated three times. Finally, the fabrics were immersed in a suspension of Ludox HS silica (~5 wt.%) and then dried in an oven at 80 °C overnight.

[0082] Manufacturing Fluorine-Free Oleophobic Fabric

[0083] Synthesized as described above tree A thin layer of fluorine-free oleophobic coating was formed on the pre-treated fabric by dip-coating or spray-coating with oil at room temperature (Figure 4). The cotton fabric was coated three times and then dried in an oven at 100°C overnight. An oleophobic PET fabric was prepared by the same method except that it was cured at 200°C for 1 h. [Example 2]

[0084] This example describes a film of the present disclosure.

[0085] FIG. 7 shows an example of a branched pendant PDMS resin. The PDMS resin comprises a PDMS polymer with a PDMS backbone. The PDMS polymer can be formed using a multifunctional precursor (e.g., a bifunctional precursor having at least two acrylate groups). The PDMS resin can be colorless.

[0086] FIG. 8 shows an example of a PDMS resin. The PDMS resin is an example of a branched pendant PDMS resin. The PDMS resin has a PDMS skeleton and Contains siloxane bondsBranched PDMS polymers include those that can be formed using multifunctional precursors (e.g., precursors having at least three vinyl groups). [Example 3]

[0087] This example provides a method for forming a layer of the present disclosure.

[0088] Besides the graft-to method (e.g., dip coating, spray coating, emulsion / foam coating, etc.), the coating can be applied to the substrate by the graft-from method (e.g., as shown in FIG. 9). The initiator may be a reversibly deactivated radical generator, such as a compound containing one or more organic halogenated moieties (e.g., alkyl halides), or one or more alkoxyamine moieties, or a suitable chain transfer agent, such as one or more thiocarbonylthio moieties. The monomer may be one or more alkylsilyl compounds containing one or more aliphatic moieties and / or aliphatic groups. Alkyl halides have been effective in initiating the polymerization.

[0089] Oleophobic coating method via surface-initiated atom transfer radical polymerization (ATRP)

[0090] An example of synthesis: The cleaned fabric samples (~1.0 x 1.0 inches) were first rinsed with water and acetone and dried under nitrogen. The dried fabric was immersed in a solution of 2-bromo-2-methylpropionyl bromide (2 mmol), trimethylamine (1 mmol) and catalytic amount of 4-dimethylaminopyridine in 30 mL of tetrahydrofuran (THF) at room temperature for 24 hours, followed by rinsing with THF and ethanol. The fabric functionalized with ATRP initiator was then immersed in a solution of alkylsilyl monomer, CuBr, and N,N',N'',N''-pentamethyldiethylenetriamine in DMF (molar ratio of CuBr / PMDETA is 0.5-1) for 24 hours. The resulting coated fabric was then washed with THF and dried to produce a fabric with an oleophobic coating.

[0091] The SEM images of the pristine and oleophobic fabrics are shown in Figure 10. A uniform coating layer on the fabric surface was observed. Photographs of the oleophobic fabrics made of different materials can be seen in Figure 11.

[0092] Although the present disclosure has been shown and described with reference to specific embodiments, it will be understood by those skilled in the art that various changes in form and detail can be made therein without departing from the spirit and scope of the present disclosure.

Claims

1. A layer comprising one or more PDMS resins, each PDMS resin comprising: i) and / or ii) i) one or more poly(dimethylsiloxanes), each poly(dimethylsiloxane) containing one or more poly(dimethylsiloxane) moieties; and Optionally, the poly(dimethylsiloxane) independently comprises one or more pendant groups having the following structure: wherein R is independently selected from alkyl groups and -O-SiOR' groups within said poly(dimethylsiloxane), and R' is independently selected from alkyl groups within the -O-SiOR' groups; ii) one or more polymers, each polymer comprising: one or more backbones selected from linear or branched poly(dimethylsiloxanes), hydrocarbon polymers, polyacrylate polymers, poly(methacrylates), poly(styrenes), poly(vinyl esters), poly(aryl ethers), polyesters, polyurethanes, polyureas, polyamides, polyimides, polysulfones, and combinations thereof; and optionally At least one pendant group having the structure: wherein each R is independently selected from an alkyl group and an -O-SiOR' group, and the R' group is an -alkyl group. Here, the layer is a layer disposed on a part or all of the outer surface of the substrate.

2. The layer of claim 1 , wherein the one or more poly(dimethylsiloxanes) comprise linear poly(dimethylsiloxane) moieties, branched poly(dimethylsiloxane) moieties, or a combination thereof.

3. the one or more poly(dimethylsiloxanes) being In the formula, R 2 are each independently selected from H, a hydrocarbon group having 1 to 40 carbon atoms, or a -O-SiOR' group, where R' group is an alkyl group; n is 0 to 400, and m is 1 to 50,000.

4. 10. The layer of claim 1, wherein at least one of the one or more poly(dimethylsiloxanes) or linear or branched poly(dimethylsiloxanes) has one or more crosslinkable groups.

5. 5. The layer of claim 4, wherein the crosslinkable groups are selected from acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof.

6. The pendant branched PDMS is formed by polymerization of one or more tris(trialkylsiloxy)silyl vinyl compounds and trimethoxysilane vinyl compounds, wherein the alkyl moieties are each independently selected from the group consisting of: 1 ~C 40 The layer of claim 1 which is an alkyl moiety.

7. The alkyl moieties each independently represent 1 ~C 30 , C 1 ~C 10 Alkyl moiety, or C 1 ~C 5 The layer of claim 6 which is an alkyl moiety.

8. the pendant groups are selected from: and optionally, the pendant groups are covalently attached to the poly(dimethylsiloxane) resin or backbone by a linking group.

9. the one or more poly(dimethylsiloxane) moieties or the linear or branched poly(dimethylsiloxane) backbone R 2 2. The layer of claim 1, wherein the number of OSi repeat units is 0-400.

10. 2. The layer of claim 1 , wherein the poly(dimethylsiloxane) has the following structure: wherein n is 0-600, m is 0-3, and X is a crosslinkable group, including, but not limited to, acrylate, methacrylate, allyl, vinyl, thiol, hydroxyl, silanol, carboxylic acid, aldehyde, amine, isocyanate, azide, alkyne, epoxy, halide, hydrogen, and combinations thereof.

11. The layer of claim 1 , wherein the layer is a cured layer.

12. 10. The layer of claim 1, further comprising at least one crosslink between two polymer chains of a PDMS resin, which may be the same or different, and / or at least one crosslink between a polymer chain of a PDMS resin and a substrate, which may be the same or different.

13. The layer further comprises one or more cross-linking moieties selected from the following, and combinations thereof: In the formula, R 3 The layer of claim 1 , wherein is a hydrocarbon group having 1 to 40 carbon atoms and n is 0 to 600.

14. The layer of claim 1 , wherein the layer further comprises a plurality of nanoparticles.

15. 15. The layer of claim 14, wherein the plurality of nanoparticles is selected from the group consisting of silica nanoparticles.

16. The method of claim 15, wherein the weight percentage of the nanoparticles is 1-98 wt % based on the total weight of the layer.

17. The layer of claim 1, wherein the layer has a thickness of from 10 nm to 300 microns.

18. 10. The layer of claim 1, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, and the like.

19. 20. The layer of claim 18, wherein the fabric is selected from cotton, PET, cotton / PET blends, nylon, polyester, spandex, silk, wool, viscose, cellulosic fibers, acrylic, polypropylene, blends thereof, leather, and combinations thereof.

20. The layer of claim 1 , wherein the substrate is a fabric having a superhydrophilic layer disposed on a portion of an exterior surface of the fabric.

21. The layer has a capacitance of 22 mJ / m 2 10. The layer of claim 1 having a surface tension of:

22. 22mJ / m 2 10. The layer of claim 1 , wherein the layer having a surface tension below 100% and the superhydrophilic layer are disposed on opposite sides of the fabric.

23. The layer of claim 1 , wherein the substrate and / or layer is fluorine-free.

24. 13. A method of forming the layer of claim 1 disposed on some or all of an exterior surface of a substrate, comprising: Coating some or all of the exterior surface of the substrate with a poly(dimethylsiloxane) (PDMS) resin or a composite nanofluid; and and curing and heating the coating at a temperature of the PDMS resin coating or a coating formed from the composite nanofluid. wherein the layer of claim 1 is formed on some or all of an exterior surface of the substrate.

25. The PDMS resin comprises: i) one or more poly(dimethylsiloxane) resins comprising one or more poly(dimethylsiloxane) moieties; wherein, optionally, the poly(dimethylsiloxane) resin comprises one or more pendant groups having the structure: wherein R is independently selected from alkyl groups and -O-SiOR' groups within said poly(dimethylsiloxane), and R' is independently selected from alkyl groups within the -O-SiOR' groups; ii) one or more polymers, a backbone selected from linear or branched poly(dimethylsiloxane), a hydrocarbon polymer, a polyacrylate polymer, a poly(methacrylate), a poly(styrene), a poly(vinyl ester), a poly(aryl ether), a polyester, a polyurethane, a polyurea, a polyamide, a polyimide, a polysulfone, and combinations thereof; and at least one pendant group having the structure 25. The layer of claim 24, wherein each R is independently selected from an alkyl group and a -O-SiOR' group, and the R' group is an alkyl group.

26. 25. The method of claim 24, wherein the composite nanofluid comprises a PDMS resin, one or more nanoparticles, and optionally a solvent, chloroform, tetrahydrofuran, and combinations thereof.

27. 25. The method of claim 24, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, and the like.

28. The method of claim 24 , wherein the substrate has a plurality of nanoparticles disposed thereon.

29. The method of claim 24, wherein the substrate is fluorine-free.

30. 25. The method of claim 24, wherein the coating is spray coating, dip coating, floating knife coating, direct roll coating, padding, calendar coating, foam coating, or a combination thereof.

31. 25. The method of claim 24, further comprising pre-treating the substrate.

32. 32. The method of claim 31, wherein the pretreatment is a chemical treatment, a physical treatment, a primer treatment, or a combination thereof.

33. 32. The method of claim 31, wherein the pretreatment comprises coating some or all of the exterior surface of the substrate with a non-metal oxide, a metal oxide, or a combination thereof.

34. 25. The method of claim 24, further comprising contacting the substrate with silica nanoparticles.

35. The method of claim 24, wherein the coating and curing is repeated 1 to 20 times.

36. 25. The method of claim 24, further comprising providing an additional surface roughness to the layer.

37. 37. The method of claim 36, wherein additional surface roughness is applied to the layer by nanofabrication, electrospinning, force spinning, extrusion, mechanical stamping, abrasion, etching, or a combination thereof.

38. 1. A method for forming a layer comprising poly(dimethylsiloxane) disposed on a portion or all of an exterior surface of a substrate, the method comprising: The method includes contacting a substrate having a plurality of functional groups capable of initiating polymerization of a dimethylsiloxane precursor with a reaction mixture, the reaction mixture comprising one or more dimethylsiloxane precursors, and (i) one or more radical initiators; or (ii) one or more metal catalysts and one or more activators comprising one or more amines; In this manner, a layer is formed that includes a poly(dimethylsiloxane) layer disposed on the surface of the substrate.

39. 40. The method of claim 38, wherein the substrate is a fabric, fiber, filament, glass, ceramic, carbon, metal, wood, polymer, plastic, paper, film, concrete, brick, and the like.

40. 40. The method of claim 38, wherein the substrate has a plurality of nanoparticles disposed thereon.

41. 39. The method of claim 38, wherein the substrate is fluorine-free.

42. 40. The method of claim 38, further comprising pre-treating the substrate.

43. 43. The method of claim 42, wherein the pretreatment is a chemical treatment, a physical treatment, a primer treatment, or a combination thereof.

44. 43. The method of claim 42, wherein the pretreatment comprises coating some or all of the exterior surface of the substrate with a non-metal oxide, a metal oxide, or a combination thereof.

45. 40. The method of claim 38, further comprising contacting the substrate (optionally having a poly(dimethylsiloxane) layer) with silica nanoparticles.

46. 39. The method of claim 38, wherein the contacting is repeated 1 to 20 times.

47. 40. The method of claim 38, further comprising providing an additional surface roughness to the layer.

48. 48. The method of claim 47, wherein additional surface roughness is applied to the layer by nanofabrication, electrospinning, force spinning, extrusion, mechanical stamping, abrasion, etching, or a combination thereof.

49. An article of manufacture comprising one or more layers according to claim 1.

50. 50. The article of manufacture of claim 49, wherein the article of manufacture is a fabric, a garment, a food packaging, eyeglasses, a display, a scanner, an airplane coating, sporting equipment, a building material, a window, a windshield, a corrosion resistant coating, an anti-icing coating, a cooler, or a light.